Analisa Penurunan Produksi Lempung Terhadap Pengaruh Curah Hujan Dengan Metode Regresi Linier - Lakon Utamakno; Agus Budianto; Enggar Priambodo (PROMINE, 2018)
The mining industry in Indonesia plays an important role as the source of state income and the part of industrial progress of a nation. The majority of mining industry in Indonesia is an open pit., including clay mine that mined by United Tractors Semen Gresik Ltd in Temandang Village, Tuban. An open pit is a mining method that is directly exposed to the free air because it is above the earth’s surface. Therefore, weather factor greatly affects the productivity of the open pit apart from the factors of work effectiveness and material hardness. The result of the study showed that Temandang area has rainfall 135 mm/month. The average of the small production was 76.000 tons per month, so it becomes the researcher’s attention to analyze how great the rainfall influenced the production decrease. To achieve the production capacity target, an analysis by using linear regression equation, in which equation formula of the best statistical test result is as follow : Log P = 0,5025 x [ log {(Pr x JK)1,99 x (CH)-0,001}] + 0,0013. The calculation result by the mathematical model equation above showed that the effect of rainfall on production decrease was very small. Thus, the working hour and productivity greatly affected the production. So, if the production needs to be increased, then the working hour must be increased